A RAPID MASS SPECTROMETRIC METHOD FOR THE SIMULTANEOUS ANALYSIS OF BARIUM, CADMIUM, AND STRONTIUM IN FORAMINIFERA SHELLS - Lea D.W.; Martin P.A. (My University, 1996)
Recent developments in inductively coupled plasma mass spectrometry (ICP-MS) make it possible to simultaneously measure a suite of trace elements of paleoceanographic interest in foraminifera shells from deep-sea sediments. Here we present an ICP-MS method that allows determination of precise Cd/Ca, Ba/Ca, Sr/Ca, and Mn/Ca ratios in purified foraminifera shell samples as small as 25 μg. The method utilizes a combination of isotope dilution for Ba and Cd determination and internal standardization for Ca and Sr determination. Long term reproductibility of the method is 2-3% for the elemental ratios. The principal advantages of the method are that all four elemental ratios of paleoceanographic interest are generated simultaneously for a single sample of purified foraminiferal carbonate, minimizing sample size requirement, reducing analysis time, and improving correlation between proxies.